2016
DOI: 10.3847/1538-4357/833/2/135
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Most Massive Overdensity Through Hydrogen (Mammoth). I. Methodology

Abstract: Modern cosmology predicts that a galaxy overdensity (e.g., protocluster) will be associated with a large intergalactic medium gas reservoir, which can be traced by Lyα forest absorption. We have undertaken a systematic study of the relation between Coherently Strong intergalactic Lyα Absorption systems (CoSLAs), which have the highest optical depth (τ) in the τ distribution, and mass overdensities on the scales of ∼10-20 h −1 comoving Mpc. On such large scales, our cosmological simulations show a strong correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 104 publications
3
90
0
Order By: Relevance
“…In order to assess how well Ly-α absorption traces large scale, high density regions, we consider the correlation be- Figure 5. The relationship between δ m and δ τ eff on 15 h −1 cMpc scales (following Cai et al 2016). Left to right, the panels show the results from Sherwood, EAGLE and Illustris.…”
Section: Relationship Between Mass and Effective Optical Depth On 15 mentioning
confidence: 99%
See 3 more Smart Citations
“…In order to assess how well Ly-α absorption traces large scale, high density regions, we consider the correlation be- Figure 5. The relationship between δ m and δ τ eff on 15 h −1 cMpc scales (following Cai et al 2016). Left to right, the panels show the results from Sherwood, EAGLE and Illustris.…”
Section: Relationship Between Mass and Effective Optical Depth On 15 mentioning
confidence: 99%
“…Applying insight obtained from a 256 3 h −3 cMpc 3 collisionless dark matter simulation, Lee et al (2016) have used this method to successfully detect a galaxy overdensity at z = 2.44 in the COSMOS field, as well as cosmic voids at z ∼ 2.3 (Krolewski et al 2018). The second method -which we focus on in this work -is to search for the most massive overdensities at z = 2-4 from a large survey volume using strong, coherent Ly-α absorption along the line of sight (Cai et al 2016). This approach is more effective at redshifts where the density of bright background sources is too low for tomography.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optically selected quasar halo masses at z ∼ 1 − 3 are consistent with the typical halo mass of ∼ 10 12 M⊙ at that epoch Coil et al 2007;White et al 2012), suggesting they do not reside in very biased regions. In fact, recently, Cai et al (2016) found that the masses of protoclusters which are traced by Lyα forest absorption are much more massive than those of typical quasars at z ∼ 2 − 3. At higher redshift z > 3, Shen et al (2007) showed that optical quasar halo masses are more massive with M ∼ (4 − 6) × 10 12 h −1 M⊙, implying that almost all luminous quasars could be associated with cluster progenitors.…”
Section: Introductionmentioning
confidence: 99%